Effects of unsupportive social interactions, stigma, and symptoms on patients with myalgic encephalomyelitis and chronic fatigue syndrome - McManimen, Stephanie L. (J Community Psychol, 2018)
Prior research has found a heightened risk of suicide in patients with myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). It is possible that a number of factors including stigma, unsupportive social interactions, and severe symptoms could lead to the development of depression, suicidal ideation, and heightened risk of suicide in this patient population. Prior studies have indicated that patients often report the legitimacy of their illness being questioned by family, friends, and even their physicians. This study aimed to determine whether stigma experienced, social support, symptomology, and functioning may be associated with depression and endorsement of suicidal ideation (SI) in patients with a self-reported diagnosis of ME or CFS. Findings indicated that participants that endorsed both SI and depression, in contrast to those that did not, experienced more frequent unsupportive social interactions in the form of blame for their illness, minimization of its severity, and social distancing from others. In addition, 7.1% of patients with ME and CFS endorsed SI but do not meet the criteria for clinical depression These findings highlight the importance of stigma and unsupportive social interactions as risk factors for suicidal thoughts or actions among patients with ME and CFS. Community psychologists have an important role to play in helping educate health care professionals and the public to these types of risk factors for patients marginalized by ME and CFS.